الكشف عن التلوث بفطور التخزين والأفلاتوكسينات في بذور فول الصويا - المغربي صباح; حسن محمود; عليو نهى (Latakia University Journal -Biological Sciences Series, 2018)
تم الحصول من تسع عينات بذور فول صويا محلية ومستوردة على /242/ عزلة نقية تتبع ل18 جنساً فطرياً، حيث عزلت على مستنبتي PDA,MSA وورق الترشيح، وكان أكثر الأجناس انتشارًا جنس Aspergillus، إذْ وصلت نسبة التلوث فيه إلى 88.33% في بعض العينات، ومن الأنواع المهمة التابعة له والتي ظهرت في معظم العينات A. flavus، A. parasiticus، A. niger، كما ظهرت أجناس أخرى تليه في الأهمية منهاPenicillium,Fusarium,Rhizopus,Absidia,Mucor,Alternaria,Trichoderma. قدرت الأفلاتوكسينات الكلية (B1,B2,G1,G2) في العينات بطريقة الأعمدة الدقيقةMinicolumn Aflatest باستخدام جهاز Vicam Flurometer، فَتَبيَّن أن كل العينات ملوثة بالأفلاتوكسينات، وبلغ أعلى تركيز لها 28PPB في عينة محلية، ولم يظهر المحتوى الرطوبي للبذور علاقة واضحة بتركيز الأفلاتوكسينات فيها، في حين انخفضت نسبة إنبات البذور عموماً نتيجة الإصابة الفطرية، وبشكل خاص في المعاملات التي لم تطهر فيها البذور سطحياً على مستنبت PDA وورق الترشيح. A total of /242/ fungal isolates belonging to /18/ genera have been obtained from nine samples of local and imported soybean seeds. The isolation was on PDA, MSA media and blotter paper. The most prevalent genus was Aspergillus where the contamination percentage was 88.33% in some samples, and the most important species were A. flavus, A. parasiticus, A. niger, followed by other genera Penicillium, Fusarium, Rhizopus Absidia, Mucor, Alternaria, Trichoderma. The total Afaltoxins (B1, B2, G1, G2) were assessed by minicolumn aflatest method using vicam Flurometer where all samples were contaminated with Aflatoxins; and the highest percentage was 28ppb in local sample. The moisture content of the seeds did not show obvious relationship with the Aflatoxins concentration while the percentage of seeds germination affected by fungal infection; and it was low in general, especially on the non-sterile seeds on PDA media and blotter paper.